ASSESSMENT OF SMALL AND MEDIUM ENTERPRISES GROWTH IN PUNJAB STATE OF INDIA - Garg, Ankit (International Journal of Research -GRANTHAALAYAH, 2015)
A strong industrial base is required for the socially and economic development of any country. The paper explores the advantages and disadvantages of small and medium scale enterprises with a comprehensive review on various aspects of ICT adoption. The study addresses the ICT adoption in their Small and Medium scale enterprises. There is significant difference between the SMEs growth that employed ICT adoption and that did not employed ICT adoption. Small and Medium Enterprises are considered to be the backbone of Punjab Economy.